Pengaruh Clash Detection Pada Proses Perencanaan Biaya Pada Laboratorium PUT - Izzudin, Alwan; Widiasanti, Irika (Universitas Batanghari Jambi, 2024)
One effort to avoid repetitive work due to errors in construction project planning can be detected from the start by implementing BIM (Building Information Modeling) which can carry out collision analysis (Clash detection) in each discipline of structural work, architecture, MEP and other disciplines. Before the existence of BIM, clashes that occurred in the building construction process were one of the factors causing work costs to increase. So implementing Building Information Modeling is one effort to avoid these problems. In this research, clash detection analysis will be carried out in the PUT Lab building in the structural, architectural and MEP work disciplines. The stages carried out in this research were first carrying out 3D Modeling using Autodesk Revit software on the PUT Lab building, then carrying out clash detection analysis using Autodesk Naviswork software and calculating the cost budget plan for each job affected by clash detection. After carrying out clash detection, clashes can be found that occur in the structural, architectural and MEP work disciplines which after calculating the budget plan can save work costs of up to 80 million rupiah.